Electrospinning Fabrication and Enhanced Performance of 3D Li3V2(PO4)3/C Fiber Membrane as Self-standing Cathodes for Li-ion Battery. (10th September 2016) - Jing, Mao-xiang; Li, Jing-quan; Pi, Zhi-chao; Zhai, Hong-ai; Chen, Li-li; Yao, Shan-shan; Xiang, Jun; Shen, Xiang-qian; Xi, Xiao-ming; Xiao, Ke-song
Abstract: A three-dimentional(3D) long-range networking Li3 V2 (PO4 )3 /C fiber membrane was fabricated by a modified electrospinning method and a hot-press calcination process. The combined use of polyacrylonitrile (PAN) and polyvinylpyrrolidone (PVP) promotes the growth of Li3 V2 (PO4 )3 crystals on the surface of the conductive carbon fibers. The adopted hot-press process is favorable to achieve a flexible 3D long-range networks. The Li3 V2 (PO4 )3 /C fiber membrane calcined at 800 °C for 20 h with a high specific surface area of 186.4 m 2 /g and a wide pore size distribution can be used as self-standing, binder-free cathodes and exhibits excellent electrochemical performances. The discharge capacity is up to 196.8, 150.4 and 145.2 mAh/g at the current density of 0.1 C, 5 C and 10 C, respectively. After the rate tests, the Li3 V2 (PO4 )3 /C fiber membrane cathode still exhibits an excellent cycle stability at 5 C with a discharge capacity of 143.4 mAh/g after 850 cycles. These high performances are ascribed to the enhanced electronic and ionic conductivities owing to the 3D long-range conductive networks, well-crystallized Li3 V2 (PO4 )3 particles in-situ grown on the surface of carbon fibers and the novel binder-free, self-standing structural characterics.